PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PEGAWAI(Studi pada Kantor Badan Keuangan Daerah Kabupaten Pamekasan) - jurnalmap map; Pahrianto ÔÇì; Chamariyah ÔÇì; Subijanto ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT This research was conducted at the Regional Finance Agency Pamekasan Regency with a total sample of 62 people. The results showed that simultaneously, leadership style, work discipline, and organizational citizenship behavior had a very significant effect on employee performance. Partially, leadership style, work discipline, and organizational citizenship behavior have a significant influence on the performance of employees of the Regional Financial Institutions Pamekasan Regency. Thus, it can be said that all independent variables partially have a significant influence on the performance of employees of the Regional Finance Agency Pamekasan Regency; and the work discipline variable has a very dominant influence in influencing the performance of employees of the Regional Finance Agency Pamekasan Regency. Keywords: Leadership style (X1), The discipline of work (X2), Organizational Citizenship Behavior (X3) and Performance of Employees (Y).